1990
DOI: 10.1113/jphysiol.1990.sp018280
|View full text |Cite
|
Sign up to set email alerts
|

A study of the developmental changes in outward currents of rat ventricular myocytes.

Abstract: SUMMARY1. In ventricular muscle of rat heart, the action potential undergoes a major dlevelopmental change in shape in the days and weeks immediately after birth. Potassium (K+) currents which may affect the shape of the action potential have been studied using a whole-cell voltage-clamp technique with single cells from the v-entricles of rats aged 1-10 days. All recordings were made at 22-23 'C.2. Three discrete ages were chosen, 1-day (cells isolated within 24 h of birth), 5-day, and 10-day rats. These paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
2
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 39 publications
11
63
2
1
Order By: Relevance
“…I to channel density increases steeply from birth to 1 month of life in the rat, as shown by our data (Table 3) and in agreement with the literature. 15,16 At variance with I to , we found that I Ca,L density is not affected by postnatal growth (Table 2), because it remains unaltered during development, as reported by Katsube et al 22 and in contrast to Gomez et al 21 Hormonal systems play a major role in controlling the maturation of rat cardiac myocyte functional properties. Importantly, the densities of I to and I Ca,L are regulated by thyroid hormones in the rat cardiac ventricle.…”
Section: Molecular Effects Of Prenatal Co Exposurecontrasting
confidence: 38%
See 3 more Smart Citations
“…I to channel density increases steeply from birth to 1 month of life in the rat, as shown by our data (Table 3) and in agreement with the literature. 15,16 At variance with I to , we found that I Ca,L density is not affected by postnatal growth (Table 2), because it remains unaltered during development, as reported by Katsube et al 22 and in contrast to Gomez et al 21 Hormonal systems play a major role in controlling the maturation of rat cardiac myocyte functional properties. Importantly, the densities of I to and I Ca,L are regulated by thyroid hormones in the rat cardiac ventricle.…”
Section: Molecular Effects Of Prenatal Co Exposurecontrasting
confidence: 38%
“…It is apparent that at 2 weeks after birth, the AP profile from Ctr is nearly identical to that recorded from CO-exposed rats (A). The AP duration (APD), as expected, 15,16 is quite long; in these cells, the phase of rapid repolarization appears to be slowed down, and the plateau phase is long. With development (4 weeks old), the AP from Ctr myocytes shows the expected decrease in duration and a prominent rapid repolarization phase; conversely, the AP from CO myocytes remains long (B).…”
Section: Data Analysis and Statisticsmentioning
confidence: 87%
See 2 more Smart Citations
“…In neonatal rodent ventricle, I to,f and I to,s (whose density is paralleled by Kv4.2/4.3 and Kv1.4 expression, respectively) show similar contributions to total I to, while in adults the former contributes over 90% (2,11,27,28). In the neonatal myocardium, the AP is longer than in the adult, and AP shortening with maturation coincides with an increase in myocardial I to density and channel isoform switch (28).…”
Section: Developmental Stagementioning
confidence: 92%